A ASSISTÊNCIA TÉCNICA À AGRICULTURA PAULISTA - REYDON, BASTIAAN PHILIP (Cadernos de Ciência & Tecnologia, 1989)
O Estado de São Paulo é a única unidade da Federação não filiada ao sistema nacional de assistência técnica e extensão rural, coordenado pela Empresa Brasileira de Assistência Técnica e Extensão Rural (EMBRATER). Nesse Estado, a assistência técnica à agricultura esteve e ainda está a cargo da Secretaria de Agricultura, que mantém um conjunto de órgãos e entidades voltados para esse fim. O presente trabalho analisa o processo evolutivo da assistência técnica oficial em São Paulo, a partir da década de 40, e o seu papel na tecnificação da agricultura paulista. Distinguem-se quatro fases no decorrer desse processo: fomento agrícola (1942-48), prestação de serviços (1949-58), extensão rural (1959-67) e assistência técnica (a partir de 1967), com a criação da Coordenadoria de Assistência Técnica Integral (CATI). As mudanças institucionais transcorreram paralelamente a modificações no conteúdo ou significado da própria assistência técnica. Tais mudanças expressam a evolução da agricultura paulista do ponto de vista das transformações capitalistas que nela tiveram curso. TECHNICAL ASSISTANCE TO AGRICULTURE IN SÃO PAULO Abstract The State of São Paulo is the only unit of the Federation not affiliated to the national system of technical assistance and rural extension coordinated by the Brazilian Enterprise for Technical Assistance and Rural Extension (EMBRATER). In this state, technical assistance to agriculture was and still is the responsability of the Secretary of Agriculture who maintains a complex of organs and entities for this purpose. The present study analyzes the evolutionary process of official technical assistance in São Paulo beginning in the 1940's, and its role in the technical development of agriculture in São Paulo. Four phases are distinguished during the course of this process: agricultural incentives (1942-48), rendering of services (1949-58), rural extension (1959-67) and technical assistance (beginning in 1967), with the creation of CATI. Institutional changes took place parallel to modifications in the content or significance of technical assistance itself. Such changes express the evolution of agriculture in São Paulo from the point of view of the capitalistic transformations which took place within it.